Influence of extracts of krill and chironomus larvae as feed attractants on growth, survival and feed utilisation in fry of European perch Perca fluviatilis Linnaeus, 1758 - Sirakov, Ivaylo; Stoyanova, Stefka (Indian Journal of Fisheries, 2018)
Technological stages of European perch (Perca fluviatilis Linnaeus,Â 1758) farming and feeding norms satisfying its nutritional requirements are not well studied. A critical moment in farming of this species in recirculation systems is the transition from live feed to commercial pelleted feed. The aim of current research was to evaluate the influence of two attractants viz., extracts from krill and chironomus larvae as feed supplements for European perch (P. fluviatilis) fry on their survival, growth and feed utilisation. European perch fry were distributed in three experimental groups, viz., F0: fed non-supplemented control feed; Fk: fed krill extract supplemented feed and Fch: fed feed supplemented with chironomus extract. Survival of European perch supplemented with krill extract was 46% as compared to 26% in control group and 30% in fish supplemented with chironomus extract (p<0.05). The highest final weight and specific growth rate were observed in perch fed feed supplemented with chironomus extract but the differences between the krill-supplemented and control groups were not significant (p>0.05). Feed conversion ratio (FCR) in fish supplemented with chironomus extract was 1.91 which was significantly lower by 32.7% than control fishes and by 29.5% lower than fish fed with krill extract supplemented feed (p<0.01). The addition of krill extract to the feed of European perch fry improved survival rate of fry, while higher growth performance was demonstrated in fish fed with chironomus extract supplemented feed.